1995
DOI: 10.3109/00048679509075901
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Structured Diagnostic Interviews: CIDI and SCAN

Abstract: The relationship between and the inter-rater reliability of the Composite International Diagnostic Interview (CIDI) and the Schedules for Clinical Assessment in Neuropsychiatry (SCAN) for anxiety and depressive disorders were explored. The CIDI and the SCAN were administered by trained interviewers in counterbalanced order. A subsample of interviews was observed to determine the inter-rater reliability of the instruments. Subjects were 101 patients accepted for treatment at an Anxiety Disorders Clinic; 29 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 11 publications
3
70
0
1
Order By: Relevance
“…A few investigators have argued that, at this stage of development, it is not appropriate to choose between the two approaches to interviewing. They have therefore argued against reporting sensitivity and specificity, as this requires that one measure be the standard against which to judge the other (Andrews et al 1995). However, most authorities probably agree that a systematic clinical assessment is the standard by which to assess lay measures (Spitzer, 1983 ;Anthony et al 1985 ;Helzer et al 1985 ;Romanoski et al 1988 ;Wittchen, 1994 ;Kessler et al 1998).…”
Section: The Difference Between the Two Methods Of Systematic Intervimentioning
confidence: 99%
“…A few investigators have argued that, at this stage of development, it is not appropriate to choose between the two approaches to interviewing. They have therefore argued against reporting sensitivity and specificity, as this requires that one measure be the standard against which to judge the other (Andrews et al 1995). However, most authorities probably agree that a systematic clinical assessment is the standard by which to assess lay measures (Spitzer, 1983 ;Anthony et al 1985 ;Helzer et al 1985 ;Romanoski et al 1988 ;Wittchen, 1994 ;Kessler et al 1998).…”
Section: The Difference Between the Two Methods Of Systematic Intervimentioning
confidence: 99%
“…The interviews were administered by two psychiatrists (EDM, FJT) trained and certified at the WHO centre in Groningen, the Netherlands. Most of the studies about the psychometric properties of the SCAN have only examined earlier versions or parts of the current version [1,27]. Rijnders et al [29] tested the psychometric properties of the integral SCAN 2.1.…”
Section: Dsm-iv Axis-i Diagnosismentioning
confidence: 99%
“…However, the results of CIDI clinical reappraisal studies varied across other settings. Some studies showed the CIDI diagnoses to have poor agreement with diagnoses based on the SCAN clinical interview (Wing et al, 1990) in a community sample (Brugha et al, 2001) and others showing agreement to be either good (Andrews et al, 1995) in a patient sample or excellent (Jordanova et al, 2004) in a primary care provider sample. This variation in results raises, with much higher concordance in patient samples than community samples, raises the possibility that respondent motivation is more of an issue than problems with question wording.…”
Section: B Responding To the Challenges: Validity Of Diagnosesmentioning
confidence: 99%